Valorizando subprodutos das produções de óleo de soja e etanol: síntese e análise técnico-econômica da produção de biolubrificantes em biorrefinarias - Martins, Christian de Oliveira (2024)
Despite oil-based products still dominate the market, there is a growing use of bio-based alternatives (called biolubricants) enhanced with chemical modifications. The main paths for the production of these biolubricants are esterification and trans-esterification. The process usually uses long-chain alcohols and fatty compounds such as acids and fats, with catalysts like enzymes, which can reduce the environ-ment impact. The production of these products can be done with by-products from other industrial processes, such the soybean oil deodorizer distillate (SODD), from the soybean oil production, and fusel oil, generated in the alcoholic fermentation of sugarcane. Therefore, this study aims at the design and techno-economic analysis of the biolubricant production, consuming these aforementioned by-products via an en-zymatic path using Pseudomona fluorencens lipase. Since there is not appropriate thermodynamic characterization of the substances present in the chosen system, this research uses several predictive methods. In addition, the phase equilibrium was es-timated using a simplified approach of pseudocomponents creation, reducing the number of components applied on simulation from dozens of pure components in SODD to only 22. The purification step consists on three parts: evaporation and recy-cle of unreacted fusel oil, product distillation and purification of the generated glycerin. The processes adapted to the context of the state of São Paulo, with the application of a location factor. A minimum attractiveness rate of 16% was used and an uncer-tainty analysis based on Monte Carlo simulations was employed to verify the uncer-tainty in the minimum selling price. Thus, the minimum selling price was 3.51±0.32 USD/kg, 41.5% lower than the price of traditional lubricants and 80.5% lower than the average of biolubricants. Even though the product is still a lubricant base, not a final product, the low price indicates that process can be a interesting option from an eco-nomic point of view.